Environmental, social, governance disclosure and corporate sustainable growth: Evidence from China - Wang, Nannan; Li, Dayao; Cui, Dengfeng; Ma, Xiaolong (Frontiers in Environmental Science, 2022)
The ultimate goal of business development is to achieve sustainable corporate growth and maximize shareholder wealth. Whether and how ESG disclosure affects sustainable growth needs to be further explored. Combining stakeholder theory and signaling theory, a panel data test based on 300 listed companies in Shanghai and Shenzhen in China finds that ESG disclosure can positively promote sustainable growth compared with companies that do not disclose ESG disclosure, and the higher the level of ESG disclosure, the greater the promotion effect on sustainable growth; and ESG disclosure further enhances sustainable growth by reducing financing constraints and enhancing human capital. In addition, the positive relationship between ESG disclosure and corporate sustainable growth is particularly pronounced for nonenvironmentally sensitive industries and when external environmental uncertainty intensifies. Our findings enrich the research related to ESG disclosure, provide motivation to motivate firms to consciously practice ESG disclosure from a sustainable growth perspective, and contribute to a more detailed understanding of the mechanisms of ESG disclosure and sustainable corporate growth.